2013
DOI: 10.1590/s2176-94512013000300024
|View full text |Cite
|
Sign up to set email alerts
|

Angle Class I malocclusion treated with lower incisor extraction

Abstract: In planning orthodontic cases that include extractions as an alternative to solve the problem of negative space discrepancy, the critical decision is to determine which teeth will be extracted. Several aspects must be considered, such as periodontal health, orthodontic mechanics, functional and esthetic alterations, and treatment stability. Despite controversies, extraction of teeth to solve dental crowding is a therapy that has been used for decades. Premolar extractions are the most common, but there are sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…The clinical case reported herein corroborates the findings in the literature which highlight that extraction of a mandibular incisor might be a good solution to correct mandibular dental crowding, 3 , 7 , 8 considering the through diagnosis of all issues involved. A set-up might be useful to aid this approach with a view to assessing the implications of extracting a mandibular incisor as well as avoiding an increased overjet.…”
Section: Final Considerationssupporting
confidence: 87%
“…The clinical case reported herein corroborates the findings in the literature which highlight that extraction of a mandibular incisor might be a good solution to correct mandibular dental crowding, 3 , 7 , 8 considering the through diagnosis of all issues involved. A set-up might be useful to aid this approach with a view to assessing the implications of extracting a mandibular incisor as well as avoiding an increased overjet.…”
Section: Final Considerationssupporting
confidence: 87%
“…Therefore, it may be concluded that extraction of the lower incisor is most effective in adults with crowding; furthermore, it is stable for at least a year after alleviation. Hegde et al [ 54 ], Barbosa [ 55 ], and Valli de Almeida et al [ 48 ] reported similar results as well as Zhylich and Suri [ 56 ] who established individual indications for extraction of one of the mandibular incisors. On the contrary, Kahl-Nieke et al [ 57 ] while evaluating postretention crowding and incisor irregularity found that stripping is more stable than extraction of one of the lower incisors in a long-term follow-up evaluation, although in insignificant manner.…”
Section: Discussionmentioning
confidence: 66%
“…O tempo de tratamento foi em média de 4 anos. Acredita -se que esta ausência de uma linha média dentária mandibular não afeta a oclusão, estética, saúde periodontal, ou a estabilidade 20,21,22 .…”
Section: R E V I S ãO D a L I T E R At U R Aunclassified